Exploring effects of discussion on visual attention, learning performance, and perceptions of students learning with STR-support. (January 2018) - Hwang, Wu-Yuin; Li, Yung-Hui; Shadiev, Rustam
Abstract: In this study, we aimed to explore effects of discussion on visual attention, learning performance, and perceptions of non-native English speaking students attending lectures in English in learning environments supported by Speech-to-Text Recognition (STR) system. One experiment was carried out with 60 students who were assigned into the control (n = 30) and experimental (n = 30) groups. Students in the control group attended lectures without discussing lectures content whereas students in the experimental group attended lectures and discussed lectures content. Our result showed that students in the experimental group had higher fixation time during two lectures compared to their counterparts in the control group. We also found that students in the experimental group had higher fixation count during the first lecture compared to the control group but there was no difference between the two groups in fixation count during the second lecture. Our results demonstrated that the experimental group outperformed the control group on both tests. In addition, most students in the two groups had high perceptions towards usefulness of STR-text for learning; however, no differences were found between the two groups in their perceptions towards STR-text. Based on our results, we suggest that learning activities, such as student discussion, need to be introduced during lectures in order to stimulate active learning, which in turn, enhances students' learning and comprehension of lecturing content. Discussion may encourage and facilitate students to take more active role in their learning. Highlights: The experimental students had higher fixation time and count during two lectures. The experimental students outperformed the control students on both tests. Most students had high perceptions towards usefulness of STR-texts for learning.